Synergy of antioxidant and M2 polarization in polyphenol‐modified konjac glucomannan dressing for remodeling wound healing microenvironment - Huiyang Li; Xiaoyu Liang; Youlu Chen; Kaijing Liu; Xue Fu; Chuangnian Zhang; Xiaoli Wang; Jing Yang (Wiley, 2023)
Abstract Effective skin wound healing and tissue regeneration remain a challenge. Excessive/chronic inflammation inhibits wound healing, leading to scar formation. Herein, we report a wound dressing composed of KGM‐GA based on the natural substances konjac glucomannan (KGM) and gallic acid (GA) that accelerates wound healing without any additional drugs. An in vitro study showed that KGM‐GA could not only stimulate macrophage polarization to the anti‐inflammatory M2 phenotype but also decrease reactive oxygen species (ROS) levels, indicating excellent anti‐inflammatory properties. Moreover, in vivo studies of skin wounds demonstrated that the KGM‐GA dressing significantly improved wound healing by accelerating wound closure, collagen deposition, and angiogenesis. In addition, it was observed that KGM‐GA regulated M2 polarization, reducing the production of intracellular ROS in the wound microenvironment, which was consistent with the in vitro experiments. Therefore, this study designed a multifunctional biomaterial with biological activity, providing a novel dressing for wound healing.